Preoperative thyroid-stimulating hormone associated risk of differentiated thyroid cancer in patients with thyroid nodules - M, Al Essa (Cellular and Molecular Biology, 2021)
In an assessment of risk for differentiated thyroid cancer (DTC) in individuals with human papillary thyroid cancer (PTC) and thyroid nodules a cohort prospective study was undertaken to establish the significance of preoperative thyroid-stimulating hormone (TSH) levels. Confirmed histologically PTC cases in one tertiary care center, and matched healthy individuals were tested for TSH, T3, T4 and T4 free total. The ORs and 95% confidence intervals have been calculated using conditional logistic regression models (CI). The blood TSH levels were related to the higher risk of PTC for men (OR,0,09; 95% Ci, 04–0,21, 95% CI and women) compared with the middle tertile of the TSH levels in the normal range (OR,0,07; 95 percent CI, 0,04–0,1). Over the normal range of TSH levels, an elevated PTC risks were connected amongst women (OR 0,09; 95% CI, 0,04–0,21) but not amongst men (OR,0,07; 95% CI, 0,04–0,1). With an increase in TSH level in the normal range between men and women, the risk for PTC reduced (Ptrend=0.041 and 0.0001). The risk of PTC related to TSH levels has been dramatically elevated above the normal range for men and TSH values below the normal range for women.